Interaksi Politik dan Media: Dari Komunikasi Politik ke Politik Komunikasi - Ghazali, Effendi (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
There has been a shift on mode of analysing politics and mass media. Heavily influenced by socio-psycological approach, media initially was treated as political mean to create particular effects. In the light of this kind of analysis Indonesia witnesses tight control of the state over the mass media. The analysis of the politics of the media, then increasingly attracting more attention. The shifting leads us to an interesting fact. Not only the media perform it function as image maker, the politicians also perform better through the politics of image creation.